India's grand strategy and foreign policy: strategic pluralism and subcultures - Beitelmair-Berini, Bernhard (Taylor & Francis Group, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- Acknowledgments -- List of abbreviations -- Introduction -- Chapter 1 How to delineate India's strategic pluralism? -- Chapter 2 Strategic culture as an IR concept -- Chapter 3 India's strategic culture debate -- Chapter 4 Cleavage theory and international relations -- Chapter 5 India's grand strategic cleavages -- Chapter 6 A case study: India's Israel policy -- Chapter 7 The subculture-cleavage model: A heuristic tool to grasp strategic pluralism? -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Sicherheitspolitik; Außenpolitik; Internationale Politik; Indien; Subkultur; Pluralismus; Strategische Planung; Politische Anthropologie